Linking protective GAB2 variants, increased cortical GAB2 expression and decreased Alzheimer's disease pathology. - Fanggeng Zou; Olivia Belbin; Olivia Belbin; Minerva M Carrasquillo; Oliver J Culley; Talisha A Hunter; Li Ma; Gina D Bisceglio; Mariet Allen; Dennis W Dickson; Neill R Graff-Radford; Ronald C Petersen; et al. (PLoS ONE)
GRB-associated binding protein 2 (GAB2) represents a compelling genome-wide association signal for late-onset Alzheimer's disease (LOAD) with reported odds ratios (ORs) ranging from 0.75-0.85. We tested eight GAB2 variants in four North American Caucasian case-control series (2,316 LOAD, 2,538 controls) for association with LOAD. Meta-analyses revealed ORs ranging from (0.61-1.20) with no significant association (all p>0.32). Four variants were hetergeneous across the populations (all p<0.02) due to a potentially inflated effect size (OR = 0.61-0.66) only observed in the smallest series (702 LOAD, 209 controls). Despite the lack of association in our series, the previously reported protective association for GAB2 remained after meta-analyses of our data with all available previously published series (11,952-22,253 samples; OR = 0.82-0.88; all p<0.04). Using a freely available database of lymphoblastoid cell lines we found that protective GAB2 variants were associated with increased GAB2 expression (p = 9.5×10(-7)-9.3×10(-6)). We next measured GAB2 mRNA levels in 249 brains and found that decreased neurofibrillary tangle (r = -0.34, p = 0.0006) and senile plaque counts (r = -0.32, p = 0.001) were both good predictors of increased GAB2 mRNA levels albeit that sex (r = -0.28, p = 0.005) may have been a contributing factor. In summary, we hypothesise that GAB2 variants that are protective against LOAD in some populations may act functionally to increase GAB2 mRNA levels (in lymphoblastoid cells) and that increased GAB2 mRNA levels are associated with significantly decreased LOAD pathology. These findings support the hypothesis that Gab2 may protect neurons against LOAD but due to significant population heterogeneity, it is still unclear whether this protection is detectable at the genetic level.